Efficacy of advanced oxidation technology and lactic acid wash for controlling Escherichia coli O157:H7 in bagged baby spinach - McKay, Krista Marie (Kansas State University, 2012)
Escherichia coli O157:H7 outbreaks have been linked to leafy green produce and bagged spinach. The objective of this study was to evaluate a Photohydroionization (PHI) panel (novel advanced oxidation technology) and varying concentrations of lactic acid washes for controlling E. coli O157:H7 on baby spinach. Leaves were dip inoculated with a five-strain cocktail of E. coli O157:H7 inoculum having a concentration between 5-6 log CFU/ml. Leaves were submerged in inoculum for 30 s and dried for 1 h. Non-inoculated and inoculated leaves were washed for 30 s in food grade lactic acid diluted to concentrations of 0.5, 1.0, or 2.0% and allowed to dry for 10 min. For PHI treatment, leaves were placed under the PHI panel and treated for 1, 2, or 5 min on both sides for total treatment times of 2, 4 or 10 min. Following treatments, leaves were either sealed in low-density polyethylene bags or enumerated. Samples were enumerated at 0, 3, 7, 10, and 14 days following inoculation. Ten gram samples were diluted with sterile peptone and stomached for one min, and then 0.1 ml was plated onto sorbitol MacConkey agar with cefixime and tellurite plates that were incubated at 37°C for 24 h. For lactic acid treatments, E. coli O157:H7 populations were different (P < 0.05) compared to the control. There was no difference (P > 0.05) due to sampling time so sampling times where pooled together for each lactic acid concentration of 0.5, 1.0, and 2.0% and resulted in 2.01, 2.78, and 3.67 log CFU/g reductions, respectively. Leaves treated with 1.0% and 2.0% lactic acid had color degradation and were organoleptically unacceptable by day 14. When leaves were treated with PHI for 1, 2, or 5 min per side, E. coli O157:H7 populations were reduced 1.6, 1.49, or 1.95 log CFU/g, respectively. Leaves treated with PHI were not different from one another, but were different (P < 0.05) from the positive control. No color change occurred in leaves treated with PHI. The PHI panel and lactic acid washes of 0.5% or higher are effective in reducing E. coli O157:H7 in baby spinach.
Keywords: Escherichia coli O157:H7; Bagged spinach; Lactic acid; Advanced oxidation technology; Produce; Food Science (0359); Microbiology (0410)